Influence of Tooth Loss and Malocclusions on Condylar Position: Analysis by Cone Beam Computed Tomography (Global Journal of Medical Research, 2024)
This study aimed to assess the position of the condyle in the condylar fossa using cone beam computed tomography in patients with tooth loss and malocclusion A sample of 47 patients of both genders from the Unichristus Dentistry service was selected and divided into six groups The division was as follows 1 Angle Class I patients 2 Angle Class II patients 3 Angle Class III patients 4 edentulous patients in both arches 5 edentulous upper and partially edentulous lower patients 6 patients with multiple losses All the patients underwent closed-mouth cone-beam computed tomography with exposure values of 85kVp 6 3ma and 20s of exposure The images were analyzed in sagittal and axial sections on both sides
Keywords: mandibular condyle temporomandibular joint cone beam computed tomography